AB0248 Clinical Significance of Soluble Vascular Endothelial-Cadherin and Anti-Vascular Endothelial-Cadherin Antibody in Rheumatoid Arthritis Treated with Etanercept or Adalimumab. (9th June 2015) - Banse, C.; Polena, H.; Stidder, B.; Khallil-Mgharbel, A.; Houivet, E.; Lequerré, T.; Fardellone, P.; Le Loet, X.; Philippe, P.; Marcelli, C.; Vilgrain, I.; Vittecoq, O.
Abstract : Background: The extra cellular domain of vascular endothelial-cadherin (sVE) increases in rheumatoid arthritis (RA) through TNF induction. Objectives: The aim of our study was to investigate the clinical value of sVE and anti-vascular endothelial-cadherin antibody (AAVE) in RA treated with etanercept or adalimumab combined with methotrexate, in terms of disease activity, prediction of structural prognosis and response to treatment. Methods: This was an 18-month prospective multicenter study in which patients had active RA, refractory to conventional Disease-Modifying Antirheumatic Drug (DMARD) requiring TNF antagonist. Fluctuations of sVE rates and AAVE titers were measured respectively by dot blot and ELISA at different time points over the follow-up period. Their relationship with parameters reflecting articular or systemic disease activity, progression of structural damage defined by ultrasonography (US) erosions, and response or remission to treatment based on EULAR criteria was analyzed. Results: Forty-eight patients received TNF blocking agents, i.e, etanercept (n=18) and adalimumab (n=30). Variation of sVE rates significantly correlated with that of C-reactive protein (CRP) levels at weeks 6, 12, 26 and 52 (r=0.4869, p=0.0008; r=0.3909, p=0.0087; r=0.3148, p=0.0450 and r=0.5477, p=0.0014 respectively). There was a significant decrease in sVE levels in the group with a decrease in CRP levels compared to the group with unmodified CRP (initial CRP ≤10 mg/l or initial CRP>10 mg/l with a variation of less than 50%). AAVE titers correlated with Erythrocyte Sedimentation Rate (ESR) (r=0.381, p=0.0128), CRP (r=-0.3361, p=0.0317), number of swollen joints (r=0.3102, p=0.0456) and total power doppler score (r=0.3841, p=0.0132). At baseline, AAVE was correlated with rheumatoid factors and a to lesser degree anti-CCP (respectively r=0.5801, p<0.0001 and r=0.3021, p=0.0518). Kinetics of sVE levels as well as AAVE titers were not associated with progression of US erosive score neither with the response to methotrexate/adalimumab or etanercept combination. Conclusions: sVE seems to be a biomarker associated with systemic RA activity under anti-TNF. AAVE are related to autoantibodies usually associated to RA and had stable titers under TNF blocking agents. Disclosure of Interest: None declared